Kajian Literature : Analisis Penerimaan Negara, Belanja Negara, dan Pembiayaan Negara terhadap Pertumbuhan Ekonomi - Raysharie, Puput Iswandyah; Meiliyadina, Yessyka; Imansyah, Muhammad Riko; Uke, Rizki Arfandi; Azira, Vioni; Tamila, Yuyun; Zahra, Zahra (STIE Jambatan Bulan, 2025)
This journal was made determined to inspect the impact of state income, state consumption and state funding on fiscal development. Fiscal development is an expansion in GDP which can be characterized as financial improvement which brings about expanded labor and products created in the public eye and builds the success of society. The factors utilized in this writing are State Ravenue, State Consumption, and State Funding. Investigation of this journal utilizes the writing audit strategy. The consequences of this writing show that state income, state consumption and state funding impact fiscal development.